Synthesis and Evaluation of Novel 2-Pyrrolidone-Fused (2-Oxoindolin-3-ylidene)methylpyrrole Derivatives as Potential Multi-Target Tyrosine Kinase Receptor Inhibitors - Ting-Hsuan Yang; Chun-I Lee; Wen-Hsin Huang; An-Rong Lee (Molecules, 2017)
Signaling pathways of VEGFs and PDGFs are crucial in tumor angiogenesis, which is essential in solid tumor progression and metastasis. This study reports our strategy for designing and synthesizing a series of novel 2-pyrrolidone-fused (2-oxoindolin-3-ylidene)methylpyrrole derivatives as potential multi-target tyrosine kinase receptor inhibitors. The target compounds were obtained by condensation of 5-substituted oxindoles with N-substituted 2-pyrrolidone aldehyde 7 in satisfactory yields. Of these, 11 and 12 had the highest potency and, compared to sunitinib, showed: (1) significant increase in anti-proliferation of various cancer cells with a favorable selective index (SI); (2) higher inhibitory potency against both VEGFR-2 and PDGFRβ. The molecular modeling results showed that, in terms of VEGFR-2 binding, the synthesized products had a similar binding mode to sunitinib but with tighter interaction.